Civil society and the 2030 Agenda. An assessment of the implementation of SDG-actions in the Metropolitan District of Quito - Cisneros, Paul; Cabrera-Barona, Pablo; López, Víctor (Iberoamerican Journal of Development Studies, 2020)
Coordination between multiple centers for decision-making and types of actors, across scales and sectors, is critical to improving the effectiveness of the implementation of Agenda 2030 and the Sustainable Development Goals (SDGs). This challenge is particularly crucial for metropolitan arrangements in developing countries where State capacity is weak, and people often lack resources to act upon the problems they face. In the Metropolitan District of Quito, various centers of decision- making implement actions to address policy problems through coordination with third sector organizations. In principle, coordination should lead to better policy implementation; however, we know very little about how this system behaves and of its outcomes. In this article, we analyze three issues: first, we look at the distribution of SDG-actions implemented by the system’s actors; second, we study the participation of different types of civil society organizations in the implementation of these actions; finally, we explore the  association of civil society involvement and the effectiveness of policy implementation.
Keywords: SDGs; policy implementation; policy effectiveness; civil society; Quito